EXTENDED ABSTRACT: RE‐OS GEOCHRONOLOGY AND CHEMOSTRATIGRAPHY OF THE MAIKOP SERIES SOURCE ROCKS OF EASTERN AZERBAIJAN. (15th June 2018) - Washburn, A. M.; Hudson, S. M.; Selby, D.; Abdullayev, N.; Shiyanova, N.
Abstract : The Oligocene – Miocene Maikop Series is a world‐class source interval and is the most important source rock for the petroleum systems of the South Caspian Basin and surrounding region. The Maikop is a thick (up to 3 km) succession of silty mudstones with intervals of high organic carbon content. However correlation of organic‐rich intervals within the South Caspian Basin and beyond to basins of the Eastern Paratethys is problematic. Current age constraints are based primarily on microfaunal assemblages, but the assemblages are lacking in precision and are sparsely dispersed. This study provides a numerical age datum for Maikopian strata that may be used to improve correlation of organic‐rich intervals both locally and regionally. The age date obtained was produced via Re‐Os isotope geochronology. Of the five sample suites analyzed, one Re‐Os data‐set yielded an isochron of 17.2 ± 3.2 Ma. Re‐Os data sets that failed to produce statistically meaningful isochrons provide qualitative age constraints by comparing calculated initial 187 Os/ 188 Os ratios from these samples to 187 Os/ 188 Os ratios in seawater through time.